Comparative antibacterial properties of zinc oxide microstructures and silver nanoparticles grown on PVDF-HFP films against Staphylococcus aureus and Escherichia coli - Nguyen, Quang Hung; Baji, Avinash; Nguyen, Tien Thanh; Truong, Vi Khanh (International Journal of Innovative Research and Scientific Studies, 2025)
The rise of antibiotic-resistant bacteria, particularly Escherichia coli and Staphylococcus aureus, poses a critical threat to public health and food safety, as these pathogens are increasingly detected in processed foods. This study evaluates the antibacterial potential of inorganic particle/polymer composites by incorporating silver (Ag) nanoparticles and zinc oxide (ZnO) microstructures into poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) films with micropillar surfaces. PVDF-HFP@Ag and PVDF-HFP@ZnO films were fabricated using solvent casting and hydrothermal growth methods, respectively, and their microstructures were characterized by FESEM, EDX, and AFM analyses. Antibacterial activity was tested against E. coli (ATCC 11303) and S. aureus (ATCC 25923) using a Live/Dead™ BacLight™ staining protocol and confocal laser scanning microscopy (CLSM). PVDF-HFP@Ag films reduced S. aureus viability to 0.6% ± 1.1% and E. coli to 41% ± 3.7%, while PVDF-HFP@ZnO films showed enhanced efficacy against E. coli (1.36% ± 0.98%) and suppressed S. aureus (3.8% ± 6%). These effects are attributed to synergistic mechanisms, including membrane disruption, ROS generation, and metal ion toxicity. The findings demonstrate the potential of these composites as scalable, non-antibiotic antimicrobial materials for food-contact surfaces and active packaging, offering a promising strategy to mitigate antimicrobial resistance and foodborne pathogens.